RESPON BEBERAPA KULTIVAR PADI SAWAH PADA PENGAIRAN SISTEM GENANGAN DALAM PARIT - Syamsuddin Syamsuddin; D. Indradewa (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Efficiency of water use in paddy rice irrigation system is necessary to increase cropping intensity. Development of rice cultivars that are responsive to adequate soil moisture with high yield and efficient use of water is required for tropical paddy fields. The research was conducted in Sleman district of Yogyakarta province, from April to August 2011. The study was conducted on some selected rice cultivars to be cultivated on soil saturated culture (SSC) system to asses the response of cultivars that can produce high grain yield. Experiment was using randomized block design (RBD) and environment factors as replications. Control treatment was rice field. Rice cultivars used are IR.64, Ciherang, Inpari-1, Inpari-2, Inpari-3, Inpari-4, Inpari-10, Inpari-6 Jete, Cigeulis, Ciliwung, Luk Ulo, Way Apo Buru, Widas, Bondoyudo, Silugonggo, Tukad Petanu, Batang Piaman, Cibogo, Dodokan, Sarinah, OM.5637, WS.63-22-1-1-3-3, Inpari-8, Situ, Bagendit, and Cimelati. The results showed that the cultivars Cimelati and Sarinah was a cultivar response to the SSC system compared to other cultivars. The Cimelati cultivar grain yield potential was 25.02 g/hill and Sarinah was 21.45 g/hill. The yield using SSC system was higher compared to rice fields system.